AN ANALYSIS OF MARKETING MAJOR STUDENT ON ENGLISH SPECIFIC PURPOSE AT SMKN 1 ACEH BARAT DAYA - Aswarni; Moetia, Meristika (English Language Teaching Methodology, 2024)
The purpose of this study was to ascertain what instructional resources SMKN I Aceh Barat Daya's marketing students require and analyzing student’s needs in learning English in this school. This research was also influenced by the marketing students' background, that the material provided did not specifically address the marketing department and the teachers only used English textbooks in general material. This research used descriptive qualitative as the research method. The instruments used to collect data are questionnaires and interview. Data analysis in this study is analysis Data Reduction, Data Display, and Conclusion Drawing. The results at this study showed that the teacher still use general for vocational schools and ESP is not yet implemented at SMKN I Aceh Barat Daya. Second, the data interview indicated that the English language skill most needed by marketing students is speaking. In addition, teacher and students agreed that speaking is a helpful skill to support their future work.